Safety of 23 Gauge Transconjunctival Sutureless 3 Port Pars Plana Vitrectomy for Vitreoretinal Diseases - Ahmad, Asad Aslam Khan, Syed Raza Ali Shah, Nadeem Ahmad, Qasim Lateef Chaudry, Chaudary Nasir (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the safety of 3 port pars plana 23 gauge trans-conjunctival sutureless vitrectomy for vitreoretinal diseases. Material and Methods: A prospective study was conducted at the Institute of Ophthalmology, Mayo Hospital Lahore from July 2010 to December 2010. All patients were admitted in the eye ward from the outpatients department. Total 30 patients were included in the study. Male to female ratio was 70:30. Mean age of patients was 45.5 years. Those included had idiopathic epiretinal membrane (ERM), diabetic vitreous hemorrhage, traumatic vitreous haemorrhage, vitreous haemorrhage secondary to Eale’s disease, diabetic macular edema, macular hole, Diabetic (tractional retinal detachment) TRD and dislocated lens. Outcome measures were recorded at baseline, 1 day, 1 week and 1 month, 2 months and 3 months post operatively. Applanation tonometery, intra & post-operative complications, ancillary tests such as ocular coherence tomography (OCT) and ultrasound were done as required. Results: Intra-operative complications noted were retinal tear 9% (2.7 patients), lens touch 4% (1.2 patients), sclerotomy leak requiring stitches 35% (10.5 patients), conjunctival hemorrhage 31% (9.3 patients), cannula slippage 13% (3.9 patients), entry site break 4% (1.2 patients) and retinal touch 4% (1.2 patients). First day post-operative complications were hypotony 20%, conjunctival inflammation 30%, mild eye discomfort 23.3% & corneal edema 13.3%. No complication was noted on 7th post operative day. Conclusion: This study showed that procedure is safe and can be adopted in different vitreoretinal procedures. It is minimally invasive surgical technique that enhances the postoperative recovery and outcomes by simplifying the surgical procedure.